2023
DOI: 10.3390/agronomy13030754
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Plant Growth Promoting Rhizobacteria to Reduce Greenhouse Gases in Strawberry Cultivation under Different Soil Moisture Conditions

Abstract: One of the main causes of climate change is the emission of GHGs, and one of the sources for the generation of such gasses is agriculture via plant production. Considering the foregoing, a study was conducted to assess PGPRs in strawberry cultivation which were able to limit GHG emissions. The first experimental factor was the inoculation of plant roots with the Bacillus sp. strains DLGB3, DKB26, DKB58, and DKB 84; the Pantoea sp. strains DKB63, DKB64, DKB65, and DKB68; Azotobacter sp. AJ 1.2; and Pseudomonas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The use of microorganisms can either reduce or have no effect on CO 2 emissions, depending on a variety of abiotic (moisture conditions, C and N substrates, SOM, fertilization, etc.) and biotic (microbial strains, soil enzymes, and microbial activity) factors [37,93,94]. Previous studies have also reported no effect of fertilization rates on CH 4 emissions [93,95,96].…”
Section: Ghg Emissionsmentioning
confidence: 89%
See 1 more Smart Citation
“…The use of microorganisms can either reduce or have no effect on CO 2 emissions, depending on a variety of abiotic (moisture conditions, C and N substrates, SOM, fertilization, etc.) and biotic (microbial strains, soil enzymes, and microbial activity) factors [37,93,94]. Previous studies have also reported no effect of fertilization rates on CH 4 emissions [93,95,96].…”
Section: Ghg Emissionsmentioning
confidence: 89%
“…The net transfer of biologically fixed N directly from the bacteria to the host plant occurs concurrently with a significant transfer of photosynthetically fixed plant carbon to the N-fixing bacteria [34]. According to various studies, the inoculation of PGPM significantly reduces GHG emissions depending on the inoculation dose, the different humidity levels of the growth substrate, and the C and N availability of the soil [35][36][37]. This could be critical in evaluating and mitigating the environmental impacts of various agricultural management practices.…”
Section: Introductionmentioning
confidence: 99%
“…The studies employed a range of methods to assess the effects of the microbial strains and drought conditions on the plants. These included the following [30,31]:…”
Section: Data Collection and Measurement Methodsmentioning
confidence: 99%
“…The data used in this study were derived from two previous studies on the effects of rhizosphere bacteria on strawberry plants under water deficit and the use of plantgrowth-promoting rhizobacteria to reduce greenhouse gasses in strawberry cultivation under different soil moisture conditions [30,31].…”
Section: Description Of the Data On Microbial Strains And Drought Con...mentioning
confidence: 99%
“…Paliwoda et al [9] assessed plant growth-promoting rhizobacteria (PGPR) to determine their potential in reducing greenhouse gas emissions in strawberry cultivation. Their study involved the inoculation of various bacterial strains and manipulation of soil moisture levels to measure the emissions of NH 3 , CO 2 , N 2 O, and CH 4 .…”
Section: Impact Of Crop Management On Greenhouse Gas Emissionsmentioning
confidence: 99%